The outcome of resurgence of diphtheria in older children in a tertiary care hospital - K. R., Sachin; H., Ramesh; K. G., Sachin; E. S., Siddharth (International Journal of Contemporary Pediatrics, 2019)
Background: Diphtheria is a fatal bacterial infection which affects the mucous membranes of oropharyngeal and nasal cavity, caused by aerobic gram-positive bacteria Corynebacterium diphtheriae. With the advent of universal immunization against diphtheria the incidence of this infectious disease has declined dramatically with few developed nations having eradicated the disease. No large outbreaks have been reported in India in recent times. Methods: In present study, authors reviewed an outbreak of diphtheria in Davangere between the months of June 2017 and July 2018. Case records of children suspected to have diphtheria, admitted to hospitals affiliated to JJM Medical College, Davangere were retrospectively analysed. Results: 15 cases were suspected to have diphtheria on clinical examination. The mean age of presentation was 7.5 years. Fever, sore throat, difficulty in swallowing, neck swelling and patch in oral cavity were the common signs and symptoms. Airway compromise, myocarditis and neurological complications were noted. Antidiphtheritic serum (ADS) was tried in all 15 cases. Case fatality rate was 40%. Conclusions: Diphtheria is a resurgent problem in India. Prompt identification and early appropriate treatment is essential to prevent morbidity and mortality. Strict adherence to the national immunisation schedule should also be emphasized.